Integrated architectural approach to designing a digital ecosystem for teacher development using The Open Group framework and domain-driven design - Dossymbek, D.M; Nurbekova, Zh.K.; Dossymbek, S. (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of this study is to develop a conceptual architectural model that integrates The Open Group Architecture Framework (TOGAF) and Domain-Driven Design (DDD) to address fragmentation and structural inconsistency in digital ecosystems for Continuous Professional Development of Teachers (CPDT). In response to the growing complexity of educational platforms, a method is proposed to formalize the connection between business segments and bounded contexts within the domain layer, thereby ensuring architectural scalability and resilience. The architectural modeling was conducted using the TOGAF framework, informed by interviews, observations, and analysis of the legal and regulatory framework. The study was carried out in collaboration with JSC “Orleu,” a leading national hub for teacher development in Kazakhstan. Business processes were structured, segmented, and visualized using BPMN notation and mapped to DDD contexts. The resulting model establishes correspondences: TOGAF segment → DDD domain, business function → bounded context, process → use case, application → microservice. This mapping allows the architecture of CPDT systems to be formalized based on domain-driven semantic logic, promoting coherence and design sustainability. The proposed approach may be applied in the development of scalable educational digital platforms and microservice-ready architectures in both public and private sectors.